Perancangan Sistem Biodigester dan Instalasi Belt Conveyor untuk Pengolahan Limbah Kotoran Ayam di Desa Bontomarannu: Indonesia - Dian Ranggina; Harun Pampang; Maria Assumpta Nogo Ole; Feni Febriani; Muh. Naufal Fajar Y; Mafhul Khair Wahda; Yoel Ponipadang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bontomarannu Village, Maros Regency, possessed significant potential in the layer poultry farming sector, yet faced serious environmental problems due to chicken manure accumulation. This community service activity aimed to improve waste management efficiency through biodigester system design and belt conveyor installation as a preparatory effort for converting organic waste into renewable energy sources. The implementation method included field survey, socialization and initial training, biodigester system design with technical calculations, belt conveyor installation, initial testing of the belt conveyor device, and monitoring and evaluation. The results showed that the biodigester system was comprehensively designed with a processing capacity for chicken manure from approximately 3,200 chickens. The belt conveyor was successfully installed under the cage and functioned properly to facilitate chicken manure collection. This activity enhanced the partner's understanding of biogas technology and prepared the infrastructure for the next stage, namely biodigester installation and biogas production, which was expected to reduce environmental pollution while supporting household energy independence for poultry farmers in the future.